Braiding Sámi Diversity and Sámi Pedagogy into Early Childhood Teacher Education: An Example from Norway - Heim, Greta; Bergan, Veronica (Education Sciences, 2024)
The framework plan for kindergartens in Norway emphasizes knowledge of Indigenous Sámi culture among the core values of pedagogical practice. Preservice students in early childhood teacher education (ECTE) are thus obliged to learn about Sámi culture. We explored and developed collaborative teaching interventions for Sámi topics. We aimed to “braid” Sámi diversity into our teaching and make the lessons explorative, practical, and student-active, in line with the basics of Sámi pedagogy. The teaching emphasized how Sámi people were historically connected to the land through sustainable livelihoods and respect for natural resources. We developed the teaching interventions through action-based research in three cycles (2022–2024). Our primary material consisted of students’ responses to online surveys and group interviews. The findings show that students gained a broader understanding of diversity within Sámi culture after the interventions. They reported greater interest and better learning outcomes, especially from the active and practical lessons. The Sámi teaching content, structure, and methods explored in this study may be relevant to other ECTE or other teacher education programs, especially those related to teaching Indigenous topics to majority populations.